Peran Ulama Dalam Pelestarian Budaya Lokal Di Kabupaten Jeneponto Sulawesi Selatan Abad 20 : - Sumirah Mira; Asnawi Hidayatullah; Sumirah; Syamzan Syukur (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2025)
Ulama have an important role in preserving local culture in South Sulawesi, one of which is the Jeneponto area, both in religious, social and customary aspects. As spiritual leaders, ulama play a role in maintaining Islamic values ​​that have been acculturated with local culture, such as in mapaccing, barzanji, and songkabala. The aim of this research is to describe and explain the role of ulama in preserving local culture in Jeneponto, South Sulawesi by paying attention and considering the Islamic values ​​contained in the local culture. This research uses library research by collecting various literature that is relevant to the study of this title. The method in this research is qualitative research which is used to understand the role of ulama in preserving local culture in Jeneponto, South Sulawesi. The research findings show that, Ulama are people who have a deep understanding of religion, besides that they also understand the science of jurisprudence, memorize the Al-Qur'an and hadith and are able to speak Arabic. Ulama are considered noble figures and ulama have various roles in life. In preserving local culture specifically in Jeneponto, South Sulawesi, there are several explanations regarding the role of ulama in preserving existing local culture by paying attention to Islamic values ​​contained in the arts of mapaccing, barzanji and songkabala.